CRITICAL SOIL OPTIMIZATION STRATEGY THROUGH THE UTILIZATION OF AGRICULTURAL WASTE, LIVESTOCK, AND FISHERIES - Widnyana, I Ketut; Wiswasta, IGN Alit; Ariati, Putu Eka Pasmidi (International Journal of Research -GRANTHAALAYAH, 2020)
Critical land area in Indonesia was recorded 23.25 million ha in 2000, and increased to 77.8 million ha in 2007, efforts are needed to optimize it. However, the existence of agricultural waste, livestock waste and sewage abundant fishery potential to increase soil fertility has not been utilized to the maximum. This study aimed to determine the macro nutrient content available in waste after the fermentation process. This research is an experimental research conducted in a laboratory to find out the content of: N, P, K, C / N ratio. The method for making liquid organic fertilizer is fermentation for one month using EM4 effective microorganisms, then analyzed using Spectrometry and Titrimetry Kjeldahl. The results showed that the highest N content was in bio urine fermentation (0.126%), fish waste (0.035%) and mixed waste (0.028%); The highest P was found in cattle rumen (7.239 mg / L), bio urine (5.234 mg / L), and seaweed (4.689 mg / L), and highest K was found in fruit waste (7, 801 mg / L). The highest C / N ratio was found in seaweed (55,643%) and fruit waste (27,857%). The conclusion is that agricultural waste, livestock waste, and fisheries waste after 1 month of fermentation contain adequate nutrients for optimizing critical land.